Pengaruh ESG Risk Terhadap Nilai Perusahaan dengan Karakteristik CEO sebagai Variabel Moderasi - Widya, Widya; Mulyani, Erly (Universitas Negeri Padang, 2025)
This study examines the impact of ESG Risk on firm value, with CEO characteristics as a moderating variable. The study focuses on companies listed on the IDX ESG Leaders from 2021 to 2023, with 19 companies selected through purposive sampling. Secondary data, including ESG Risk scores from the Indonesia Stock Exchange and financial and non-financial data from annual reports, were analyzed. Firm value was measured using the price-to-book value (PBV) ratio. Moderation regression analysis was conducted using IBM SPSS Statistics version 26. The findings indicate that: (1) ESG Risk does not significantly affect firm value; (2) CEO characteristics can strengthen the influence of ESG Risk on firm value.